The Relation between the Corporate Bond-Yield Spread and the Real Economy: Stable or TimeVarying? - Sune Karlsson; Pär Österholm (Örebro University School of Business, 2019)
In this paper we assess whether the relation between the corporate bond-yield spread and the real economy has been stable over time. Using quarterly US data from 1953Q1 to 2018Q2, we estimate Bayesian VAR models which allow for drifting parameters and/or stochastic volatility and conduct formal model selection in a Bayesian setting. Our results indicate that the relation between the variables has been stable; we do, however, find strong support for stochastic volatility. We conclude that the corporate bond-yield spread's usefulness for predicting real economic activity has not changed to a relevant extent after the Great Reces-sion.
Keywords: C11; C32; C52; E44; E47; G17; 330; Bayesian VAR; Time-varying parameters; Stochastic volatility; Model selection